2016
DOI: 10.1091/mbc.e16-01-0048
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase A can block EphA2 receptor–mediated cell repulsion by increasing EphA2 S897 phosphorylation

Abstract: The EphA2 receptor plays multiple roles in cancer through two distinct signaling mechanisms. In a novel cross-talk, the β2-adrenoceptor/cAMP/PKA axis can promote EphA2 pro-oncogenic, ligand-independent signaling, blocking cell repulsion induced by ligand-dependent signaling. PKA emerges as a third kinase, besides AKT and RSK, that can regulate EphA2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(96 citation statements)
references
References 99 publications
7
84
0
Order By: Relevance
“…A recent report has shown that EphA2 Ser-897 can be phosphorylated by protein kinase A (PKA), but not by Akt, in forskolin-stimulated prostate cancer cells. 46) PKA also belongs to the AGC family and has a similar substrate recognition motif, suggesting that other AGC protein kinases may catalyze EphA2 Ser-897. It was also shown that not all prostate and pancreatic cancer cell lines, which those authors used in their experiments, 46) were sensitive to forskolin.…”
Section: Epha2 Noncanonical Signaling Transductionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent report has shown that EphA2 Ser-897 can be phosphorylated by protein kinase A (PKA), but not by Akt, in forskolin-stimulated prostate cancer cells. 46) PKA also belongs to the AGC family and has a similar substrate recognition motif, suggesting that other AGC protein kinases may catalyze EphA2 Ser-897. It was also shown that not all prostate and pancreatic cancer cell lines, which those authors used in their experiments, 46) were sensitive to forskolin.…”
Section: Epha2 Noncanonical Signaling Transductionmentioning
confidence: 99%
“…46) PKA also belongs to the AGC family and has a similar substrate recognition motif, suggesting that other AGC protein kinases may catalyze EphA2 Ser-897. It was also shown that not all prostate and pancreatic cancer cell lines, which those authors used in their experiments, 46) were sensitive to forskolin. However, EGF-induced phosphorylation of EphA2 on Ser-897 was detected in all cell lines, suggesting that the cellular context and cell environment influence the kinase of EphA2 Ser-897.…”
Section: Epha2 Noncanonical Signaling Transductionmentioning
confidence: 99%
See 3 more Smart Citations